1999
DOI: 10.1093/brain/122.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Visual control of locomotion in Parkinson's disease

Abstract: The effect of placing parallel lines on the walking surface on parkinsonian gait was evaluated. To identify the kind of visual cues (static or dynamic) required for the control of locomotion, we tested two visual conditions: normal lighting and stroboscopic illumination (three flashes/s), the latter acting to suppress dynamic visual cues completely. Sixteen subjects with idiopathic Parkinson's disease (nine males, seven females; mean age 68.8 years) and the same number of age-matched controls (seven males; nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
217
2
14

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(252 citation statements)
references
References 31 publications
19
217
2
14
Order By: Relevance
“…Decreased walking velocity can be considered as a behavioural strategy to avoid imbalance and fall, as reported by some subjects and as already seen in behavioural investigations in our cat model [28]. In addition, slow or reduced locomotion velocity by taking shorter steps was also reported for non-pathological subjects over 65 years [15], as well as in pathological cases including Parkinson's disease [2] and neuropathic patients [13]. Taken together, the similar changes in gait parameters found both with aging and in different pathologies strongly suggest that they are unlikely related directly to a specific sensory loss (unilateral vestibular deficit, herein) but rather to a reduction in self-selected walking speed.…”
Section: Locomotor Pattern Changessupporting
confidence: 78%
“…Decreased walking velocity can be considered as a behavioural strategy to avoid imbalance and fall, as reported by some subjects and as already seen in behavioural investigations in our cat model [28]. In addition, slow or reduced locomotion velocity by taking shorter steps was also reported for non-pathological subjects over 65 years [15], as well as in pathological cases including Parkinson's disease [2] and neuropathic patients [13]. Taken together, the similar changes in gait parameters found both with aging and in different pathologies strongly suggest that they are unlikely related directly to a specific sensory loss (unilateral vestibular deficit, herein) but rather to a reduction in self-selected walking speed.…”
Section: Locomotor Pattern Changessupporting
confidence: 78%
“…It has also been reported that there is an increased visual dependence perceptually in patients with PD [8]. Interest in visual dysfunction is enhanced by the possible relationships between gait disorders and visual perception [9]. Gait problems such as festination and freezing are thought to be strongly influenced by visual stimulation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this natural aging process, other factors may contribute to balance disruption facing sensory disturbance, in this population. Loss of automation in performing postural changes can increase the dependence on visual information 26 . Studies of Ickenstein et al 7 .…”
mentioning
confidence: 99%